Effects of Complex Korean Medicine Treatment on a Patient with Knee Pain and Ankylosis Following a Distal Femur Osteotomy: A Case Report - Han Bin Park; Eun Sil Heo; Dong Hwi Yoo; Won Suk Jang; Oh Bin Kwon; Ki Won Choi; Min Jin Kwon; Tae Ju Kim; Seon Woo Jang; Oh Hoon Kwon (MEDrang Inc., 2022)
Distal femur osteotomy (DFO) is a controlled surgical break of the femur performed to allow realignment of the limb. Redistribution of the load aims to correct the abnormal mechanical weight-bearing axes in patients with abnormal alignment of the lower extremities, and degenerative changes in the knee joint. This report describes a complex Korean medicine treatment for a patient complaining of knee pain and stiffness following a DFO. Post-operative care for the patient lasted 78 days with treatment including pharmacopuncture, acupuncture, herbal medicine, cupping therapy, and physiotherapy. The effectiveness of the treatments was evaluated using the numerical rating scale, range of motion of the knee, and by physical examination. After treatment, these evaluation indicators improved, suggesting that the complex Korean medicine treatment received by the patient was an appropriate treatment for knee pain and stiffness following a DFO.